Debt, Wealth, Income Distribution and Demand: A post-Keynesian Empirical Study on Turkiye - Ozan Ekin Kurt (İstanbul İktisat Dergisi)
The aim of this article is to examine effects of wealth, personal income distribution, and households’ and firms’ debt stock on aggregate demand and its components in Türkiye and characterize its demand regime. For this purpose, we examined the Turkish economy over the 1988-2019 period within a post-Keynesian framework. Our findings suggested that the proxy variable for wealth has a small but positive effect on consumption, but no effect on investment. We observed that of four personal income distribution indicators employed in econometric investigations, only one of them had some minor effect on consumption but none of them had any significant effect on investment. Household debt, probably due to mortgages, turned out to have a positive effect on total investment expenditures, which also consists of newly constructed residences, but no effect on consumption expenditures. Our econometric estimations also pointed out that business debt has a negative effect on investment. The synthesis of findings suggested that the demand regime is profit-led in Türkiye. However, calculation of growth contributions of variables indicate that functional income distribution has a minor role, but wealth and debt variables have a major role in determination of aggregate demand.